Prevalence of bacterial vaginosis in postmenopausal women in the state of Odisha, India - Madhumita Nayak; Prasanta Purohit; Alliyatri Debta; Shalini Sinha; Siris Patel; Ojaswini Patel; Padmalaya Das; Sunanda Sahoo (Al Ameen Medical College, 2020)
Background: Worldwide, only few reports are there to explain the prevalence of bacterial vaginosis (BV) as well as the association of various factors with BV in postmenopausal women. Aims and Objectives: To study the prevalence of BV and to analyze the association of various factors with BV in postmenopausal women in the state of Odisha, India. Methods: During recruitment, all the women completed a questionnaire containing socio-demographic features, medical and gynecological problems. A speculum examination of the vagina was done and a vaginal secretion was collected using BD BBL swabs for Gram staining. Diagnosis of BV was carried out by using Nugent's scoring method and a score of 4-10 was considered for abnormal or positive for BV. Results: A total of 209 postmenopausal women were recruited in this study with a median age of 54 years. As per the diagnostic criteria, the prevalence of BV was found to be 24.4%. The occurrence of BV was found to be associated with age of the women specially who were >55 years old (P=0.018), women with no formal education i.e. less than 5th standard (P=0.016), and women who were staying with 6 or more individuals in family (P<0.0001). Most of the postmenopausal women with BV were significantly associated with various clinical symptoms like abnormal vaginal discharge (P=0.001), itching/ burning of genitalia (P=0.011) and back pain (P=0.001). Conclusion: The association of various factors and clinical symptoms with BV found in this study may have implications in the health of postmenopausal women in India.